2013
DOI: 10.1080/09540121.2013.855297
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing of male partners of pregnant women in Porto Alegre, Brazil: A potential strategy for reduction of HIV seroconversion during pregnancy

Abstract: Pregnant women have a significantly higher risk of HIV acquisition during gestation than their non-pregnant counterparts due to behavioral and biological factors. Acute seroconversion during gestation results in increased HIV mother-to-child transmission rates and has been identified as a major public health challenge. In order to address potential HIV seroconversion in our pregnant patients, we conducted a prospective cohort study to evaluate the acceptability of offering HIV testing to sexual partners of HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Table 2 identifies basic characteristics of study setting and type of the included studies. Of the 44 articles included, 24 were qualitative studies [ 13 , 14 , 18 23 , 25 , 27 , 28 , 39 51 ], 10 were cross sectional studies [ 26 , 51 59 ], 3 were cohort studies [ 24 , 60 , 61 ], 3 were systematic reviews [ 12 , 16 , 17 ], 3 were randomised control trials [ 62 64 ], and 1 used mixed methods [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 identifies basic characteristics of study setting and type of the included studies. Of the 44 articles included, 24 were qualitative studies [ 13 , 14 , 18 23 , 25 , 27 , 28 , 39 51 ], 10 were cross sectional studies [ 26 , 51 59 ], 3 were cohort studies [ 24 , 60 , 61 ], 3 were systematic reviews [ 12 , 16 , 17 ], 3 were randomised control trials [ 62 64 ], and 1 used mixed methods [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies were set in a number of countries including (in order of frequency) South Africa [ 12 , 17 , 20 , 40 , 41 , 51 , 57 , 62 ], Kenya [ 12 , 17 , 50 , 53 , 58 , 61 , 63 ], Uganda [ 12 , 14 , 17 , 42 , 43 , 52 , 54 ], Malawi [ 12 , 17 , 21 , 23 , 24 , 27 ], Tanzania [ 12 , 13 , 17 , 44 , 56 ], Cameroon [ 12 , 15 , 17 , 64 ], Zambia [ 12 , 19 , 39 ], India [ 15 , 17 , 64 ], Democratic Republic of Congo [ 12 , 17 , 49 ], Mozambique [ 26 , 46 , 48 ], Brazil [ 25 , 51 , 60 ], Ethiopia [ 55 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 ] In order to curb the incidence of acute HIV acquisition during pregnancy, health units providing prenatal care associated with Hospital Conceiçao are now encouraged to offer HIV voluntary counseling and testing (VCT) to male partners of HIV negative pregnant women. [ 22 , 23 ] In a study performed at this site in 2011, 54% of male partners attended prenatal care received HIV testing; however, most obtained testing during the last few months of pregnancy. [ 23 ] In the non-study setting, health care providers at the site stated that most male partners do not attend prenatal care.…”
Section: Introductionmentioning
confidence: 99%
“…Partner testing and engagement remain cornerstones of identifying women vulnerable to HIV. Several studies describe partner HIV testing of HIV-negative pregnant women in antenatal clinics and off site [ 59 65 ]. The HOPE trial in Kenya found that home-based testing for pregnant women and their partners was cost-effective [ 66 ].…”
Section: Discussionmentioning
confidence: 99%